Wound Vitality in Decomposed Bodies: New Frontiers Through Immunohistochemistry - Bertozzi, Giuseppe; Ferrara, Michela; La Russa, Raffaele; Pollice, Giovanni; Gurgoglione, Giovanni; Frisoni, Paolo; Alfieri, Letizia; De Simone, Stefania; Neri, Margherita; Cipolloni, Luigi (Frontiers in Medicine, 2021)
Background: The question about wound vitality and estimation of wound age of production is one of the classic investigation fields of forensic sciences. To answer this, the techniques most frequently used in research studies are: immunohistochemistry (IHC), molecular biology and biochemistry. Despite the great data in the literature about the usefulness of IHC in forensic pathology, there is always a request for further studies, especially on tissues altered by putrefactive phenomena. The degradation of the tissues, in fact, is intended as the main limiting factor to the use of this technique. Scope: The aim of this pilot study was to evaluate the immunohistochemical behavior of samples collected from decomposed bodies (in different putrefaction phases) and to relate these findings to wound vitality and postmortem interval.MaterialsandMethods: Samples of skin and soft tissues were collected during autopsies executed on decomposed bodies, whose cause of death wasconcluded to be traumatic. An immunohistochemical study was performed using antibodies against CD15, CD45, IL-15, tryptase, glycophorin-A MMPs (endopeptidases involved in degrading extracellular matrix proteins: MMP-9 and MMP-2). IHC reaction was evaluated according to a qualitative method as the following legend: (0): not expressed, (+): isolated and disseminated expression, (++): expression in groups or widespread foci, (+++): widespread expression. Results: Most of the tested markers (tryptase, glycophorin, IL15, CD 15, CD 45, MMP9) showed to be highly expressed in the tissue of putrefied skin from 15 days.Discussionandconclusion: Though certainly not conclusive, this experimental application demonstrated, that a non-exclusive but combined use of multiple antibodies is appropriate to verify wound vitalityin decomposed bodies. Among them, GPA exhibited the major reliability.